2021
DOI: 10.4103/2045-9912.311498
|View full text |Cite
|
Sign up to set email alerts
|

A review on the neuroprotective effects of hyperbaric oxygen therapy

Abstract: Hyperbaric oxygen therapy, intermittent breathing of 100% oxygen at a pressure upper than sea level, has been shown to be some of the neuroprotective effects and used therapeutically in a wide range of neurological disorders. This review summarizes current knowledge about the neuroprotective effects of hyperbaric oxygen therapy with their molecular mechanisms in different models of neurological disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 174 publications
(181 reference statements)
0
1
0
1
Order By: Relevance
“…HBO therapy is used to treat diseases by inhaling pure oxygen in an environment above atmospheric pressure. In recent years, studies both at home and abroad have shown that HBO has a good therapeutic effect on DOC, which can improve the GCS, CNPVSS, and GOS scores of patients with DOC with different etiologies, improve their prognosis, and shorten coma times (Ahmadi & Khalatbary, 2021 ; Joshua et al., 2022 ; Y. S. Liu, Liu, et al., 2022 ; M. Liu, Li, et al., 2022 ; S. Y. Zhang et al., 2017 ). In this study, we analyzed patients with DOC who had been treated over the past 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…HBO therapy is used to treat diseases by inhaling pure oxygen in an environment above atmospheric pressure. In recent years, studies both at home and abroad have shown that HBO has a good therapeutic effect on DOC, which can improve the GCS, CNPVSS, and GOS scores of patients with DOC with different etiologies, improve their prognosis, and shorten coma times (Ahmadi & Khalatbary, 2021 ; Joshua et al., 2022 ; Y. S. Liu, Liu, et al., 2022 ; M. Liu, Li, et al., 2022 ; S. Y. Zhang et al., 2017 ). In this study, we analyzed patients with DOC who had been treated over the past 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies report that hyperbaric oxygen therapy has a neuroprotective effect in the treatment of neurological injuries [22]. Therefore, we also used hyperbaric oxygen therapy for nerve injuries.…”
Section: Discussionmentioning
confidence: 99%
“…[12] Тип ушкодження (за AOSpine): ушкодженні СМ. Крім того, низка експериментальних досліджень дала змогу виявити інші потенційні механізми нейропротекторного ефекту ГБО [13,14]: 1) пригнічення апоптозу, 2) зменшення оксидантного стресу, 3) зменшення запалення, 4) стимулювання ангіогенезу, 5) зменшення набряку спинного мозку, 6) посилення автофагії тощо. Апоптоз -це форма запрограмованої загибелі клітин, яка спостерігається при різних захворюваннях і патологічних станах, зокрема при травматичних ушкодженнях СМ.…”
Section: обговоренняunclassified